Increasing interval to prostaglandin from 17 days to 19 days in an MGA-prostaglandin synchronization system for heifers - D.W. Nix; G.C. Lamb; V. Traffas; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1998)
Weanling Angus x Hereford heifers were purchased by a commercial heifer development operation from 12 sources. Heifers were fed a silage-based diet through an initial developmental period and then were retained or culled based on their average daily gain, pelvic area, or disposition. Of the original 591 heifers, 14% were culled. Estrus was synchronized using the Colorado MGA-Prostaglandin (PG) synchronization system with PG administered at either 17 days or 19 days after the 14th day of MGA feeding. Heifers were inseminated artificially (AI) during 30 days followed by 30 days of natural mating. Heifers given PG on day 17 after MGA had a first-service conception rate of 69.9% compared with 65.8% for heifers given PG on day 19. In the day 17 treatment, 64.2% of the heifers were inseminated artificially by 84 hr after the PG injection versus 75.1% for the day 19 treatment. Injections of PG 19 days after MGA tended to tighten synchrony of estrus. Based on source of purchase, first-service conception rates ranged from 50% to 85%, whereas overall pregnancy rates ranged from 65% to 95%. With early culling, accurate records, and pregnancy diagnosis, producers can identify reliable sources from which to purchase their replacement heifers, which should decrease costs and increase profit potential.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Replacement heifers; Artificial Insemination; Synchronization; Culling